PENGARUH ETOS KERJA DAN BEBAN KERJA TERHADAP SEMANGAT KERJA PADA PEMERINTAHAN KECAMATAN SIBOLGA KOTA - Revina Tanjung; Kaharuddin; Mansur Tanjung (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The essence of the work ethic is to see work as more than just it a way to seek income alone, but to find existence and dignity as a human being. Someone will be excited to work, if the workload given is in accordance with their abilities. The formulation of the problem in this study is Is there an influence of work ethic and workload on work enthusiasm in the Sibolga City District Government? The purpose of this study was to find out whether there is an influence of work ethic and workload on work enthusiasm in the Sibolga City District Government. The hypothesis in this study is that work ethic and workload have a positive effect on work enthusiasm at the Sibolga Kota District Government Office. This type of quantitative research with a survey approach. The population is 85 people and used as a sample. Source of data comes from primary and secondary data. Data were analyzed using descriptive analysis and quantitative analysis. The results of the determination test show that the variables of work ethic and workload can influence the variable of employee morale in the Sibolga Kota District Government, it is known from the magnitude of the coefficient of determination (R Square) that is 0.547. Work ethic and workload together or simultaneously have a positive and significant effect on the morale of employees in the Sibolga Kota District Government. Where the Fcount value is greater than the Ftable value (45.363 > 3.11). Partially, work ethic has a positive and significant effect on employee morale in the Sibolga Kota District Government. Where tcount = (2.515) is greater than ttable value (1.992), Partially the most dominant workload affects morale, meaning that the workload variable is more decisive in increasing employee morale compared to work ethic. Where the value of tcount = (4.441) is greater than the value of ttable (1.992). The multiple linear regression equation Y = 9.965 + 0.250X1 + 0.582X2 employee morale shows a positive direction